2012
DOI: 10.1093/hmg/dds046
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived epigenetic interactions between perinatal PBDE exposure and Mecp2308 mutation

Abstract: The widespread use of persistent organic polybrominated diphenyl ethers (PBDEs) as commercial flame retardants has raised concern about potential long-lived effects on human health. Epigenetic mechanisms, such as DNA methylation, are responsive to environmental influences and have long-lasting consequences. Autism spectrum disorders (ASDs) have complex neurodevelopmental origins whereby both genetic and environmental factors are implicated. Rett syndrome is an X-linked ASD caused by mutations in the epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 62 publications
(78 reference statements)
5
80
0
1
Order By: Relevance
“…Examples include studies investigating early exposure to phthalates, polybrominated diphenyl ethers, and polychlorinated biphenyls (Larsson et al, 2009; Miodovnik et al, 2011; Mitchell et al, 2012; Testa et al, 2012; Woods et al, 2012). Although the magnitude seen in the present study is relatively small, there is evidence that large increases in neurons and glia are found in human males diagnosed with autism (Courchesne et al 2011; Edmonson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include studies investigating early exposure to phthalates, polybrominated diphenyl ethers, and polychlorinated biphenyls (Larsson et al, 2009; Miodovnik et al, 2011; Mitchell et al, 2012; Testa et al, 2012; Woods et al, 2012). Although the magnitude seen in the present study is relatively small, there is evidence that large increases in neurons and glia are found in human males diagnosed with autism (Courchesne et al 2011; Edmonson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation plays an important role in neuronal development (van Bokhoven and Kramer, 2010; Schroeder et al 2011), and two recent report have provided initial evidence that low doses of PBDEs may affect DNA methylation. In one study, perinatal exposure of mice to low levels of BDE-47 (yielding brain levels of ~20–40 ng/g lipids) was reported to decrease global DNA methylation in cerebral cortex (Woods et al 2012). In another study, a similar low level perinatal exposure to BDE-47 caused a decrease of expression of a number of genes involved in DNA methylation and histone modification (Suvorov and Takser, 2011).…”
Section: Potential Mechanisms Of Pbde Developmental Neurotoxicitymentioning
confidence: 99%
“…In contrast, levels of PBDEs in human blood or other tissues, even in the most exposed individuals, are in the nanomolar range. A recent study reports that average BDE-47 levels in human brain were 20 ng/g lipids (Woods et al 2012). Various studies in animals have reported brain levels of different PBDEs ranging from 1 to 500 nM (Cheng et al 2009; Reistad et al 2006; Staskal et al 2006; Voorspoels et al 2006; Basu et al 2007; Crump et al 2008; Ta et al 2011; Koenig et al 2012).…”
Section: The Issues Of Dose/concentration and Of Potential Interactionsmentioning
confidence: 99%
“…However, Woods et al 2012 considered these factors insufficient to explain the significant increase in the number of cases of autism. Furthermore studies in monozygotic twins, discordant for autism by Hallmeyer et al 2011, indicate that there is a substantial environmental contribution to autism etiology.…”
Section: Environmental Exposures and Autismmentioning
confidence: 99%